2015
DOI: 10.1007/s13277-015-3492-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in cytochrome P450 and clinical outcomes of FOLFIRI chemotherapy in patients with metastatic colorectal cancer

Abstract: The purpose of this study is to evaluate the influence of germline polymorphisms of cytochrome P450 (CYP450) on objective response, progression-free survival (PFS) and overall suruvival (OS) in metastatic colorectal cancer (mCRC) receiving the combination chemotherapy of irinotecan, 5-fluorouracil, and leucovorin (FOLFIRI). All SNPs in CYP450, whose minor allele frequency were more than 10 %, were genotyped in 82 patients with mCRC who received first-line FOLFIRI regimen. χ (2) test or Fisher's exact test was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…21 Some SNPs are in connection with increasing risk 24 Increasing GWAS have brought new hope to identify susceptibility loci of CRC in the past decade. 21 Some SNPs are in connection with increasing risk 24 Increasing GWAS have brought new hope to identify susceptibility loci of CRC in the past decade.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Some SNPs are in connection with increasing risk 24 Increasing GWAS have brought new hope to identify susceptibility loci of CRC in the past decade. 21 Some SNPs are in connection with increasing risk 24 Increasing GWAS have brought new hope to identify susceptibility loci of CRC in the past decade.…”
Section: Discussionmentioning
confidence: 99%
“…21 Some SNPs are in connection with increasing risk of developing CRC, 22,23 some SNPs appear to lower the metastatic risk of CRC and others have been associated with the efficacy of various treatments for CRC. 24 Increasing GWAS have brought new hope to identify susceptibility loci of CRC in the past decade. Several previous large-scale meta-analysis studies of GWAS on colorectal cancer identified novel CRC risk loci at 14q22 (BMP4), 16q22 (CDH1), 19q13 (RHPN2), and 20p12, 25 genetic loci at 1q41, 3q26 (MYNN), 12q13 (ATF1/DIP2B), and 20q13 (LAMA5), 26 6p21 (CDKN1A), 11q13 (POLD3), and Xp22 (SHROOM2), 27 and 5q31, 12p13 (CCND2), and 20p12 (HAO1/PLCB1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using RCT data alone resulted in the conditional variance 0.0089 (95% CrI: 0.0000, 0.11), while the addition of cRWE gave a conditional variance of 0.010 (95% CrI: 0.0002, 0.051). Thus, the addition of cRWE reduced 40 Matsumoto 2007 41 Catalano 2009 42 Fuse 2008 43 Suenaga 2008 44 Fuse 2007 45 Hochster 2003 46 Yoshino 2007 47 Bendell uncertainty by 54% in terms of the CrI width. The addition of sRWE to RCTs and cRWE further improved precision of the intercept, slope, and conditional variance estimates.…”
Section: Dandh Modelmentioning
confidence: 99%
“…The presence of CYP3A5 has been demonstrated in normal colon (3,17,18), colon adenoma (19), and CRC (20). The CYP3A5*3 polymorphism, which can lead to reduced enzyme activity, has been associated with significantly longer progression-free survival in patients with metastatic CRC (21).…”
Section: Introductionmentioning
confidence: 99%